The ichthyofauna of the upper Neretva River - Jakob Neuburg; Thomas Friedrich; Elisabeth Haring; Sarah Höfler; Ana Maric; Saša Marić; Stephanie Popp; Predrag Simonović; Aleš Snoj; Simona Sušnik Bajec; Simon Vitecek; Alexandra Wanka; et al. (Natura Sloveniae)
Fish were sampled at nine locations of the upper Neretva River, upstream of Glavatičevo. Evidence of the endangered softmouth trout (Salmo obtusirostris) was obtained as well as the presence of other native and non-native salmonids. Genetic analysis suggests that the native brown trout (Salmo trutta) in the upper Neretva is homogeneous with no significant introgression by introduced Atlantic-lineage brown trout and quantitative catch data show that their populations are healthy with densities above 1,000 ind/ha. However, the relatively low biomass estimates may be the result of overharvesting. A new haplotype of the mitochondrial control region of the bullhead (Cottus gobio) was detected and confirmation of native S. trutta, Barbatula barbatula, Phoxinus sp., and C. gobio in the upper reaches, underlining the importance of this river stretch. The planned expansion of hydropower plants in the upper Neretva and its tributaries will have a significant negative impact on the largely untouched ichthyofauna, as is clearly demonstrated by the conditions found in the middle course of the river, which has been dedicated to hydropower production.